Progress toward a large-scale ion Talbot-Lau interferometer - Demetrio, Andrea; Müller, Simon R.; Oberthaler, Markus K. (Physical review, 2017)
The Talbot-Lau interferometer is a proven tool to perform measurements in the near-field regime. It has been extensively used for investigating the wave nature of electrons, atoms, and complex organic molecules. However, when designing devices with high geometrical acceptances, which would be desirable when dealing with low-intensity sources of particles, the alignment requirements become much more stringent. Furthermore, if the particles are charged, the influence of external fields becomes quickly non-negligible when increasing the length of the device. This paper focuses on both the geometric and physical constraints of an ion Talbot-Lau interferometer, with emphasis on the scaling of such constraints with the size of the device. Mathematical formulas which set limits on the critical parameters are derived and applied to a test setup for protons.
Gesehen am 27.03.2018